2005
DOI: 10.1266/ggs.80.173
|View full text |Cite
|
Sign up to set email alerts
|

DNA variation in the metallothionein genes in wild rice Oryza rufipogon: Relationship between DNA sequence polymorphism, codon bias and gene expression

Abstract: This study examines the relationship between DNA sequence variation and level of gene expression in four metallothionein genes from wild rice Oryza rufipogon . The nucleotide diversity was 0.0028 to 0.0117 over the entire coding and non-coding region, and it was negatively correlated with gene expression for three type 2 metallothionein genes. In contrast, codon bias and percent of preferred codons correlated positively with gene expression. These results indicate that the intensity of natural selection depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…The shape of the tree within the sequence type A was star-like. These results supported the hypothesis that O. rufipogon recently expanded into tropical and subtropical regions (Barbier et al, 1991;Yoshida et al, 2004;Miyashita et al, 2005;Yoshida and Miyashita, 2005).…”
Section: Polymorphic Sites In the Pita Region Of O Rufipogonsupporting
confidence: 87%
See 1 more Smart Citation
“…The shape of the tree within the sequence type A was star-like. These results supported the hypothesis that O. rufipogon recently expanded into tropical and subtropical regions (Barbier et al, 1991;Yoshida et al, 2004;Miyashita et al, 2005;Yoshida and Miyashita, 2005).…”
Section: Polymorphic Sites In the Pita Region Of O Rufipogonsupporting
confidence: 87%
“…Therefore, we employed the amino acid distance analysis of Miyata et al (1979) to estimate whether the observed nucleotide differences between O. rufipogon and O. officinalis at replacement sites of Pita could be related to physicochemical differences. The analysis revealed that the number of nonconserved amino acid differences in the Pita was 73, which was 52% of the total number of amino acid differences in the Pita (Supplementary table 2 (Yoshida et al, 2004;Miyashita et al, 2005;Yoshida and Miyashita, 2005). As observed in the Adh2 and 10 nuclear loci (Tang et al, 2006), a dimorphic pattern was also detected in O. rufipogon Pita.…”
Section: Polymorphic Sites In the Pita Region Of O Rufipogonmentioning
confidence: 79%
“…Coupled with the previous studies based on the genetic markers such as SINE, RAPD and SSR (Cheng et al, 2003;Ren et al, 2003) and nucleotide variations in nuclear genes (Yoshida et al, 2004;Yoshida and Miyashita, 2005;Miyashita et al, 2005;Rakshit et al, 2007), our result might provide a new insight into phylogenetic relationships of wild rice with A-genome and origin of the cultivated rice, O. sativa. Table 1 (Rozas and Rozas, 1999).…”
Section: Introductionsupporting
confidence: 75%
“…japonica and indica were included in the cluster of O. rufipogon as seen in the phylogenetic tree based on the nucleotide variation in Adh1, Adh2 and methalothionein genes (Yoshida et al, 2004;Yoshida and Miyashita, 2005;Miyashita et al 2005). This result is compatible with the hypothesis that O. sativa is originated from O. rufipogon (Oka and Chang, 1959).…”
Section: Interspecific Comparison Of Dna Variation In the Spw1 Regionmentioning
confidence: 99%
“…Once T d is determined, T e is assumed to be a random variable between 0 and T d . For N 0 , the level of nucleotide diversity in O. rufipogon is roughly one-third of that in teosintes (Clark et al 2004;Miyashita 2005), so N 0 of the wild progenitor of rice may be $300,000 given that N 2 for wild teosinte may be $900,000-1,000,000 (Eyre-Walker et al 1998). Therefore, we used a lognormal distribution with mean 3 3 10 5 and SD 0.6 3 10 5 for the prior distribution of N 0 so that the 95% interval is approximately between 2 3 10 5 and 4.4 3 10…”
Section: Simulate the Five Demographic Parameters (mentioning
confidence: 99%